Measurement of the jet mass in highly boosted t(t)over-bar events from pp collisions at root s=8TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (European Physical Journal C: Particles and Fields, 2017)
The first measurement of the jet mass mjetmjet of top quark jets produced in tt¯tt¯ events from pp collisions at s√=8s=8 TeVTeV is reported for the jet with the largest transverse momentum pTpT in highly boosted hadronic top quark decays. The data sample, collected with the CMS detector, corresponds to an integrated luminosity of 19.7 fb−1fb−1 . The measurement is performed in the lepton+jets channel in which the products of the semileptonic decay t→bWt→bW with W→νW→ν where is an electron or muon, are used to select tt¯tt¯ events with large Lorentz boosts. The products of the fully hadronic decay t→bWt→bW with W→qq¯¯¯′W→qq¯′ are reconstructed using a single Cambridge–Aachen jet with distance parameter R=1.2R=1.2 , and pT>400pT>400 GeVGeV . The tt¯tt¯ cross section as a function of mjetmjet is unfolded at the particle level and is used to test the modelling of highly boosted top quark production. The peak position of the mjetmjet distribution is sensitive to the top quark mass mtmt , and the data are used to extract a value of mtmt to assess this sensitivity.